Thin MAPb0.5Sn0.5I3 Perovskite Single Crystals for Sensitive Infrared Light Detection - Wu, Jinming; Zhang, Yongqiang; Yang, Shuang; Chen, Zhaolai; Zhu, Wei (Frontiers in Chemistry, 2022)
Metal halide perovskite single-crystal detectors have attracted increasing attention due to the advantages of low noise, high sensitivity, and fast response. However, the narrow photoresponse range of widely investigated lead-based perovskite single crystals limit their application in near-infrared (NIR) detection. In this work, tin (Sn) is incorporated into methylammonium lead iodide (MAPbI3) single crystals to extend the absorption range to around 950 nm. Using a space-confined strategy, MAPb0.5Sn0.5I3 single-crystal thin films with a thickness of 15 μm is obtained, which is applied for sensitive NIR detection. The as-fabricated detectors show a responsivity of 0.514 A/W and a specific detectivity of 1.4974×1011 cmHz1/2/W under 905 nm light illumination and –1V. Moreover, the NIR detectors exhibit good operational stability (∼30000 s), which can be attributed to the low trap density and good stability of perovskite single crystals. This work demonstrates an effective way for sensitive NIR detection.